Hydration and recognition of methylated CpG steps in DNA. - Mayer-Jung, C (1998)
The analysis of the hydration pattern around methylated CpG steps in three high resolution (1.7, 2.15 and 2.2 A) crystal structures of A-DNA decamers reveals that the methyl groups of cytosine residues are well hydrated. In comparing the native structure with two structurally distinct forms of the decamer d(CCGCCGGCGG) fully methylated at its CpG steps, this study shows also that in certain structural and sequence contexts, the methylated cytosine base can be more hydrated that the unmodified one. These water molecules seem to be stabilized in front of the methyl group through the formation C-H...O interactions. In addition, these structures provide the first observation of magnesium cations bound to the major groove of A-DNA and reveal two distinct modes of metal binding in methylated and native duplexes. These findings suggest that methylated cytosine bases could be recognized by protein or DNA polar residues through their tightly bound water molecules.